Aristotel kot multiseksist - Vezjak, Boris (Analiza (Ljubljana), 2025)
The article examines the issue of Aristotle’s sexism from the perspective of contemporary concepts of gender, science, and epistemologically responsible interpretation. Positing that his sexism is not one-dimensional, the author introduces the concept of "multi-sexism" to describe the complex biological, political, and metaphysical relationships structuring his philosophical and scientific system. The analysis reveals that Aristotle’s gender hierarchy is deeply ingrained in his scientific framework, specifically regarding nature, movement, and teleology. The article argues that the debate on Aristotle's sexism is not about moral judgment, but rather a methodological question of interpretation: how to read historically conditioned philosophical and scientificconcepts without reducing them to contemporary normative categories. Three key considerations are raised: (1) gender in Aristotle’s biology and metaphysics; (2) epistemological dilemmas in feminist philosophy of science in interpreting classical texts; and (3) reinterpreting Aristotle beyond sexually hierarchical structures. The aim is to demonstrate that understanding Aristotle as a multi-sexist is not merely a criticism, but that this approach offers a tool for a more precise analysis of the historical foundations of sexual differentiation in Western thought.
Keywords: Antična filozofija; Aristotel; biologija; feminist philosophy of science; feministična filozofija znanosti; interpretacija; interpretation; metafizika; metaphysics; seksizem; sexism